FOSTERING A SENSE OF NATIONAL PRIDE AMONG STUDENTS BY TEACHING JADID ACTIVITIES IN HISTORY LESSONS (Academia Science Repository, 2023)
The article describes feedback on the development of a sense of national pride among students by teaching the activities of Jadids in history lessons in the general education system, encouraging them to search, actually search and analyze data, teaching students such knowledge and skills as how to work with data, how and where to look for data, how to compare, what to base the comparison on.